Biological Matrices and Synthetic Meshes Used in Implant-based Breast Reconstruction – a Review of Products Available in Germany - Dieterich, M.; Faridi, A. (Geburtshilfe und Frauenheilkunde, 2013)
While autologous breast reconstruction was considered the procedure of choice for immediate breast reconstruction, there has been a shift towards implant-based breast reconstruction (IBBR) in recent years. The proven safety of silicone breast implants and the development of biological matrices and synthetic meshes have contributed to the growing popularity of this approach. Although these different products are widely used, only limited clinical data are available with regard to breast surgery. The aim of this review was to give an overview of available biological matrices and synthetic meshes and discuss their use in clinical practice.
Keywords: breast cancer; breast reconstruction; biological matrix; synthetic mesh; ADM